An Analysis Of The Development Of An Education Management Information System From A Sensemaking Perspective And The Use Of Quantitative Methods To Evaluate Educational Data Sets - Yongmao, Li; Duraipandi, Oyyappan (Journal of Neonatal Surgery, 2025)
Educational data sets are analyzed quantitatively in this work. Using sensemaking, it examines the "Education Management Information System (EMIS)" development process and its effects. Improving data utilisation and EMISs' ability to back up educational decision-making is what prompted this research. Since EMISs impact the capacities of several stakeholders, researchers carefully analyze their design and operation throughout their manufacturing process. Educators, administrators, and legislators are all considered stakeholders. Using a sensemaking method, researcher assess how the EMIS has affected the stakeholders' ability to understand and apply the data for strategic purposes. In order to do this, researchers will have to observe user behavior and assess the system's ability to support data-driven insights or judgments. At the same time, the research analyzes educational data sets administered by the EMIS using quantitative methodologies. Important parts of this process include checking the data for correctness, completeness, and usability and figuring out how these quantitative analyses help with bettering educational results and policy choices. Important performance measures include data relevance, data integrity, and the effect of data-driven choices on pedagogical approaches. The results should provide recommendations on how to enhance the design of EMIS in order to help students become more comfortable with quantitative approaches and enhance their sensemaking abilities in the classroom. The main goal of the project is to bring together different viewpoints in order to promote data-informed and more effective methods of school administration. Ultimately, this ought to result in improved educational achievements.